1982
DOI: 10.3382/ps.0612473
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Premolt Production on Postmolt Performance with Explanation for Improvement in Egg Production Due to Force Molting

Abstract: Performance of force-molted hens as influenced by premolt production was determined in two experiments using 720 Babcock hens. Hens selected to be laying at a low (41%), average (59%), and high (75%) rate of production were divided into two groups. One half of the hens were force molted (FM) and the other half served as controls (CON). On completion of the fasting period, blood was collected for chemical analyses from 10 hens per group. These hens were then necropsied and weights of the ovary, oviduct, liver, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

1984
1984
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 13 publications
2
16
0
3
Order By: Relevance
“…After moulting the calcium metabolism in hens, and especially its absorption in the intestine, calcium transport to the oviduct for the shell synthesis in the uterus and also calcium deposition in medullary bones are improved. A correct complex diet, especially a mineral diet during moulting and at the start of a new reproductive cycle, decides on the effectiveness of the consumer egg production (Roland and Brake, 1982). It can be stated that the above information has been confirmed by our observations.…”
Section: Discussionsupporting
confidence: 78%
“…After moulting the calcium metabolism in hens, and especially its absorption in the intestine, calcium transport to the oviduct for the shell synthesis in the uterus and also calcium deposition in medullary bones are improved. A correct complex diet, especially a mineral diet during moulting and at the start of a new reproductive cycle, decides on the effectiveness of the consumer egg production (Roland and Brake, 1982). It can be stated that the above information has been confirmed by our observations.…”
Section: Discussionsupporting
confidence: 78%
“…Gildersleeve et al (1983) found the Ca and P levels in the control and molting groups as 26.6-5.1 mg/dL and 6.9-4.43 mg/dL respectively. Roland and Brake (1982) also determined the serum, Ca and P levels in the control and molting groups to be 23-4.6 mg/dL and 14-4.4 mg/dL respectively. Hens in a long term fasting program (10 days) had lower Ca and P levels than the short term fasting Ca-P levels (Yalçın, 1998).…”
Section: Biochemical Parameters and Histopathological Findings In Thementioning
confidence: 99%
“…Forced molting is defined as a set of management practices to promote stress, inducing birds to stop producing eggs and the partial molting of the feathers (Roland & Brake, 1982). The objective of forced molting is to rest the reproductive system of layers for some time in order to recover their production capacity and to increase the longevity of layers for further 25 to 30 weeks, as well as to improve egg quality, reducing losses caused by poor eggshell quality (Berry, 2003).…”
Section: Introductionmentioning
confidence: 99%